PENGARUH MOTIVASI KERJA DAN PERSEPSI ORGANISASI TERHADAP KINERJA PEGAWAI PADA BADAN NARKOTIKA NASIONAL PROVINSI SULAWESI TENGGARA - ., Sahyunu; M., Suyuti H.; Anita, Asri (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2020)
This study aims to determine the effect of work motivation and perceived organizational support on employee performance at the National Narcotics Agency of Southeast Sulawesi Province. The sample in this study were 54 respondents taken by census at the BNN Office of Southeast Sulawesi Province. This study uses multiple linear regression analysis tools. The results of the study that simultaneous work motivation and perceived organizational support had a positive and significant effect on employee performance. Partially work motivation and perception of organizational support have a positive and significant effect on employee performance.